Pengembangan Media Pembelajaran Fisika Berbantuan 3D Application Scratch Pada Topik Tekanan Hidrostatis - Dicky Kurniawan Saputra; Riki Perdana (MAGNETON: Jurnal Inovasi Pembelajaran Fisika UNWIRA, 2024)
Physics learning that takes place in schools today tends to be monotonous, namely the teacher provides material, formulas, example problems, and exercises done by students so that students feel bored and think that studying physics is difficult. Teachers need to provide learning media that are interesting and can improve understanding of concepts, enthusiasm, motivation, and activeness of students in learning. The purpose of this study was to determine the feasibility of learning with Scratch-assisted learning media. The results showed that Scratch-based learning media on the topic of hydrostatic pressure is feasible to use in the learning process at school, with an overall feasibility level of 93.75%. All aspects in the indicator are included in the very feasible category except for the access aspect in indicator number 5 in the feasible category. Even so, overall this learning media has a very high level of feasibility so it is suitable for use as a learning media in the teaching and learning process at school. The scratch application in the learning process causes students to be more enthusiastic and active, think creatively, and be able to work together in groups.